SITUATION THE CONTAINS OF SOME MICROBIAL AGENTS IN MILK AND DAIRY PRODUCTS FOR CHILDREN UNDER 36 MONTHS IN VIETNAM 2019-2021 (Vietnam Journal of Community Medicine, 2022)
Objective: To determine the level of contamination of some microbial agents in milk and dairyproducts for children under 36 months.Subjects and methods: Cross-sectional descriptive study, sampling and testing 4 commonmicrobiological criteria of 1,500 samples of milk and dairy products circulating in 6 major cities/provinces. The results were compared with Decision No. 46/2007/QD-BYT, 19/12/2007 of theMinister of Health.ResultS: Milk and dairy products for children under 36 months with the greatest risk of microbialcontamination are dairy fats. The most commonly infected organism is Listeria monocytogenes. E.coli:13.33% of liquid cream samples; 11.11% of avocado samples exceeded the limit. Staphylococusaureus: 12.22% Cream powder samples; 5.00% of the skimmed milk powder samples exceeded thepermissible limit. Salmonella: 6.33% of cheese samples, 8.33% of liquid Cream samples; 8.88%of avocado samples, 7.77% of fat samples exceeded the allowable limit. Listeria monocytogenes:5.00% whey powder sample, 5.00% milk concentrate sample, 3.67% cheese sample, 6.67% buttersample, 10.00% fat sample and 6.00% milk product sample fermentation beyond the allowable limit.Conclusion: Contamination of E.coli, Staphylococus aureus, Salmonella and Listeria monocytogenesstill occurs in some milk and dairy products intended for children under 36 months of age, posing arisk of food poisoning for children.
Keywords: Pollution, microorganisms, milk and dairy products.